Measurement of ultralow permeability. Issue 4 (12th November 2015) - Ramakrishnan, T. S.; Supp, Michael G.
Abstract : A permeability measurement method based on perturbed pressure decay between a source and a sink communicating through a porous medium is formulated. Nonideality of gas as well as corrections due to adsorption are considered. The method allows us to infer permeability at a given rock and fluid state. The accuracy of the method may be evaluated through comparison with theoretical decay characteristics and its modal amplitudes. A quantitative evaluation of the experimental inference is therefore possible. Based on the pressure decay theory, an apparatus built in our laboratory for measuring permeability is presented. As a secondary output, data analysis also provides porosity. The lowest permeability that the present apparatus is capable of characterizing is about 0.3 nm 2, and with additional improvements, capability down to 0.05 nm 2 is anticipated. Where a steady‐state permeameter is pragmatic, excellent agreement between the two measurements is showed, validating the method. Measurements in synthetic samples also show that the method is accurate. Porosity data from a standard helium pycnometer confirm the porosity obtained from the decay method. © 2015 American Institute of Chemical Engineers AIChE J, 62: 1278–1293, 2016